Economic burden of herpes zoster in Latin America: A systematic review and meta-analysis. Issue 7 (30th December 2022) - Javier Balan, Dario; Bardach, Ariel; Palermo, Carolina; Alconada, Tomás; Sandoval, Macarena; Nieto Guevara, Javier; Gomez, Jorge; Ciapponi, Agustin
ABSTRACT: This systematic review describes herpes zoster (HZ) economic burden in terms of healthcare resource use and cost outcomes in the Latin America and Caribbean (LAC) region. We searched online databases from 1 January 2000 to 20 February 2020 to identify eligible publications. We identified 23 publications that reported direct costs, indirect costs, and resources associated with HZ and its complications. The primary direct medical resources reported in the different studies were visits to doctors, transportation, days in the hospital, nursing, medication schedules, and physical therapy. Direct total costs per patient ranged from 99.99 to 4177.91. The highest cost was found in Brazil. Direct costs are, in average, 81.39% higher than indirect costs. The cost per patient that includes postherpetic neuralgia treatment is 115% higher on average for the directs and 73% for the indirect costs. Brazil reported a higher total cost per patient than Argentina and Mexico, while for indirect costs per patient, Brazil and Argentina had higher costs than Mexico, respectively. A meta-analysis on the number of days due to HZ hospitalization, performed on non-immunosuppressed patients over 65 years of age from three studies, resulted in a cumulative measure of 4.5 days of hospitalization. In the LAC region, the economic burden of HZ and associated complications is high, particularly among high-risk populations and older age groups. Preventative strategies such as vaccination could help avoid or reduce the HZ-associated disease economic burden in the LAC region.